Microbial Signatures in Deep CO2-Saturated Miocene Sediments of the Active Hartoušov Mofette System (NW Czech Republic) - Liu, Qi; Adler, Karsten; Lipus, Daniel; Kämpf, Horst; Bussert, Robert; Plessen, Birgit; Schulz, Hans-Martin; Krauze, Patryk; Horn, Fabian; Wagner, Dirk; Mangelsdorf, Kai; Alawi, Mashal (Frontiers in Microbiology, 2020)
The Hartoušov mofette system is a natural CO2 degassing site in the central Cheb Basin (Eger Rift, Central Europe). In early 2016 a 108 m deep core was obtained from this system to investigate the impact of ascending mantle-derived CO2 on indigenous deep microbial communities and their surrounding life habitat. During drilling, a CO2 blow out occurred at a depth of 78.5 meter below surface (mbs) suggesting a CO2 reservoir associated with a deep low-permeable CO2-saturated saline aquifer at the transition from Early Miocene terrestrial to lacustrine sediments. Past microbial communities were investigated by hopanoids and glycerol dialkyl glycerol tetraethers (GDGTs) reflecting the environmental conditions during the time of deposition rather than showing a signal of the current deep biosphere. The composition and distribution of the deep microbial community potentially stimulated by the upward migration of CO2 starting during Mid Pleistocene time was investigated by intact polar lipids (IPLs), quantitative polymerase chain reaction (qPCR) and deoxyribonucleic acid (DNA) analysis. The deep biosphere is characterized by microorganisms that are linked to the distribution and migration of the ascending CO2-saturated groundwater and the availability of organic matter instead of being linked to single lithological units of the investigated rock profile. Our findings revealed high relative abundances of common soil and water bacteria, in particular the facultative, anaerobic and potential iron oxidizing Acidovorax and other members of the family Comamonadaceae across the whole recovered core. The results also highlighted the frequent detection of the putative sulfate oxidizing and CO2 fixating taxon Sulfuricurvum at certain depths. A set of new IPLs are suggested to be indicative for microorganisms associated to CO2 accumulation in the mofette system.